Biotechnology - Dilemma & Strategic Response - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Scientists have used biotechnology for centuries to enhance the production, availability and quality of food. However within recent times the selective and sophisticated manipulation of genes of living organisms also referred to as bio-engineering, has ra